Anal Squamous Cell Carcinoma in Ulcerative Colitis: Can Pouches Withstand Traditional Treatment Protocols?. Issue 9 (September 2021) - Lightner, Amy L.; Vaidya, Prashansha; McMichael, John; Click, Benjamin; Regueiro, Miguel; Steele, Scott R.; Hull, Tracy L.
Abstract : BACKGROUND: Anal squamous cell carcinoma has rarely been reported in the setting of ulcerative colitis. OBJECTIVE: This study aimed to understand the prognosis of anal squamous cell carcinoma in the setting of ulcerative colitis. DESIGN: This is a retrospective review. SETTING: This study was conducted at a referral center. PATIENTS: Adult patients with both ulcerative colitis (556.9/K51.9) and anal squamous cell carcinoma (154.3/C44.520) between January 1, 2000 and August 1, 2019 were included. MAIN OUTCOMES MEASURES: The primary outcomes measured are treatment and survival of anal squamous cell carcinoma. RESULTS: Of the 13, 499 patients with ulcerative colitis treated, 17 adult patients with ulcerative colitis and anal dysplasia and/or anal squamous cell carcinoma were included in the study: 6 had a diagnosis of anal squamous cell carcinoma, 8 had high-grade squamous intraepithelial lesions, and 3 had low-grade squamous intraepithelial lesions. There were 4 men (23%) and a median age of 55 years (range, 32–69) years. At diagnosis, 6 had an IPAA, of which 5 had active pouchitis, 1 had an ileorectal anastomosis with active proctitis, 1 had a Hartmann stump with disuse proctitis, 5 had pancolitis, and 4 had left-sided colitis. Of the 6 with anal squamous cell carcinoma, all received 5-fluorouracil and mitomycin C with external beam radiation therapy. Four patients had an IPAA, all of whom required intestinal diversion or pouch excision because of treatment intolerance. At a median follow-up of 60 months, 3 patients died: one at 0 months (treatment-related myocardial infarction), one at 60 months (metastatic anal squamous cell carcinoma), and one at 129 months (malignant peripheral nerve sheath tumor); the remaining patients had no residual disease. LIMITATIONS: This study was limited because of its retrospective nature and small number of patients. CONCLUSION: Anal squamous cell carcinoma in the setting of ulcerative colitis is extremely rare. In the setting of IPAA, diversion may be necessary to prevent radiation intolerance. Careful examination of the perianal region should be performed at the time of surveillance endoscopy. See Video Abstract at http://links.lww.com/DCR/B582 . CARCINOMA ANAL DE CÉLULAS ESCAMOSAS EN COLITIS ULCEROSA: ¿PUEDE EL POUCH MODIFICAR LOS RESULTADOS DE LOS PROTOCOLOS DE TRATAMIENTO TRADICIONAL: ANTECEDENTES: La incidencia de cáncer anal de células escamosas es muy baja en pacientes con colitis ulcerosa. OBJETIVO: Comprender el pronóstico del cáncer anal de células escamosas en el contexto de la colitis ulcerosa. DISEÑO: Revisión retrospectiva. AJUSTE: Centro de referencia. PACIENTES: Pacientes adultos con colitis ulcerosa (556.9 / K51.9) y cáncer anal de células escamosas (154.3 / C44.520) entre el 1 de enero de 2000 y el 1 de agosto de 2019. RESULTADOS PRINCIPALES: Tratamiento y sobrevida del cáncer anal de células escamosas. RESULTADOS: De 13.499 pacientes en tratamiento por colitis ulcerosa, diecisiete presentaron displasia y/o cáncer de células escamosas: 6 con cáncer, 8 con lesiones intraepiteliales escamosas con displasia de alto grado y 3 con displasia de bajo grado. Cuatro son hombres (23 %) con una mediana de 55 años (rango 32-69). Al realizar el diagnóstico 6 tenían pouch, 5 con pouchitis activa; 1 con ileorecto anastomosis con proctitis activa y 1 con operación de Hartman y muñón con colitis por desuso; además 5 tenían pancolitis y 4 tenían colitis izquierda Todos los casos con cáncer anal de células escamosas (6 pacientes), fueron tratados con 5-FU mas Mitomicina y radioterapia externa. Cuatro pacientes tenían pouch, todos requirieron derivación intestinal o escisión del pouch por intolerancia al tratamiento. En la mediana de seguimiento de 60 meses, tres pacientes fallecieron: uno a los 0 meses (infarto de miocardio relacionado con el tratamiento), uno a los 60 meses (cáncer de células escamosas metastásico) y uno a los 129 meses (tumor maligno de la vaina del nervio periférico); el resto no presentaba enfermedad residual. LIMITACIONES: Revisión retrospectiva, número pequeño de pacientes. CONCLUSIÓN: El cáncer anal de células escamosas en el contexto de la colitis ulcerosa es extremadamente raro. En el contexto de IPAA, la derivación puede ser necesaria para prevenir la intolerancia a la radiación. Se debe realizar un examen cuidadoso de la región perianal en el momento de la endoscopia de control. Consulte Video Resumen en http://links.lww.com/DCR/B582 .